2019
DOI: 10.1259/bjr.20180951
|View full text |Cite
|
Sign up to set email alerts
|

The value of sonoelastography in the diagnosis of supraspinatus tendinopathy—a comparison study

Abstract: Rotator cuff tendinopathies are a prevalent cause of reduced activity or disability in the general population. Patients may present with decreased shoulder function such as painful shoulder movements, a painful arc, weakness, discomfort, and stiffness. On clinical evaluation, weak external rotators, a weak supraspinatus, and signs of impingement may be found. 1 Sonoelastography (SE) by measuring stiffness helps to assess the biomechanical and structural properties of tissues. 2 Ultrasound (USG) is an easily ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Studies about supraspinatus tendon, such as ours, also revealed that degenerative tendinopathy is associated with greater capacity of tendon deformation during elastographic evaluation. ( 16 )- ( 19 On the other hand, Baumer et al ( 20 evaluated the influence of age on supraspinatus tendon shear modulus in individuals of different ages and observed that older individuals had stiffer tendons. However, unlike our study, the measurement was carried out in the intra-muscular portion of the tendon, which does not allow the isolated evaluation of the tendon itself, but also involves the muscle belly itself.…”
Section: Discussionmentioning
confidence: 99%
“…Studies about supraspinatus tendon, such as ours, also revealed that degenerative tendinopathy is associated with greater capacity of tendon deformation during elastographic evaluation. ( 16 )- ( 19 On the other hand, Baumer et al ( 20 evaluated the influence of age on supraspinatus tendon shear modulus in individuals of different ages and observed that older individuals had stiffer tendons. However, unlike our study, the measurement was carried out in the intra-muscular portion of the tendon, which does not allow the isolated evaluation of the tendon itself, but also involves the muscle belly itself.…”
Section: Discussionmentioning
confidence: 99%
“…Vasishta et al assessed the relationship between tendon stiffness on SE and supraspinatus tendinopathy grading on MRI (Grade I, normal; Grade II, mild tendinopathy; Grade III, moderate tendinopathy; and Grade IV, marked tendinopathy) in 25 patients ( 10 ). They reported a good correlation between the supraspinatus tendon strain ratios and the MRI grade: the strain ratio decreased with increasing severity of tendinopathy.…”
Section: Resultsmentioning
confidence: 99%
“…Vasishta et al (16) reported that strain elastography shows a moderate to strong association with MRI findings of tendinopathy. That study has the closest subject to ours.…”
Section: Discussionmentioning
confidence: 99%